Development of Powerpoint Learning Media on the Material of Examining the Structure of Review Text (Poetry) Class VIII Smp Negeri 1 Moro'o - Benedikta Waruwu; Riana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The primary aim of this research is to create PowerPoint learning media specifically designed to facilitate the review of poetry structures within textual analysis, with a focus on feasibility, practicality, and effectiveness. Following the systematic approach of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), this study incorporates various methods including material expert validation questionnaires, linguistic assessments, design expert evaluations, as well as feedback from students and assessments of learning outcomes. The findings reveal the successful development of PowerPoint learning materials tailored to the needs of poetry review text analysis. Notably, feasibility evaluations demonstrated promising results, with material expert assessments achieving a revision rate of 67.3% in the initial stage and a perfect score of 100% in the subsequent revision. Linguistic assessments similarly improved from 65.7% in the first revision to 94.2% in the second. Design expert evaluations showed a significant increase from 38.9% to 94.7% between revisions. Practicality assessments from small group and field trials scored impressively at 96% and 94.2%, respectively, indicating high levels of practical application. Furthermore, effectiveness evaluations exhibited noteworthy outcomes, with a 100% success rate in small group trials and a commendable 92% success rate in field trials, underscoring substantial effectiveness. In conclusion, the developed PowerPoint learning media emerges as a feasible, practical, and effective tool for enhancing the learning process, particularly in the context of reviewing poetry structures. These findings contribute to the advancement of educational technology and instructional design practices.